Improving Student’s Mathematical Creative Thinking Ability and Self Regulated Learning using Sylver Approach - Desy Tri Damayanti; Utari Sumarmo; Rippi Maya ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This study was a pre test-post test experiment without control group design having a goal to examine the role of Prior Mathematics Ability (PMA), Sylver  approach (SA) toward student’s mathematical creative thinking ability (MCTA) and Self Regulated Learning (SRL).  The study involved  65 eleven  grade student, a PMA test, a MCTA test, and SRL scale. The study found that PMA and SA took good role on obtaining student’s MCTA, its N<Gain> and SRL. On student’s MCTA, and its N<Gain> students getting treatment with SA attained better grades than that of students taught by conventional teaching, and the  grades were still at medium level.  On SRL,  there was no different grades between students on both teaching approaches, and those grades were at fairly good  level.  The other findings, there was no association between MCTA and SRL, and students performed high perception toward SA.